Stage of task learning as a moderator of the goal-performance relationship - Mone, M. A.; Baker, D. D (Human Performance, 1989)
It was found that specific, difficult goals resulted in higher performance levels than do-your-best goals when assigned to Ss in the middle stages of learning. This is the stage when performance strategies and behavioral patterns are being established. The goals supposedly energize higher levels of application which stimulate a greater learning rate. Implication: When athletes start to learn to focus on multiple elements of performance (e.g., technique items plus strategic determinations) is the time when goal difficulty and expectations should be increased if performance improvements are to be stimulated optimally.